Penerapan Model Pembelajaran Resource Based Learning (RBL) Dalam Upaya Meningkatkan Kemampuan Penguasaan Konsep IPA - Muldiyana Nugraha (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
APPLICATION OF RESOURCE BASED LEARNING (RBL) MODEL IN EFFORTS TO IMPROVE MASTERY ABILITY OF SCIENCE CONCEPT. The study is aims to determine the improvement of the ability mastery of science concept by applying Resource Based Learning (RBL) learning model. The method used in this research is a classroom action research method consisting of three cycles, where in each cycle there are two meetings except in cycle III only one meeting. Resource Based Learning (RBL) learning model can improve students’ mastery of science concept of SMPN 3 Satap Cikulur. The improvement of students’ mastery of science is obtained from the results of data on cycle I activity that obtained an average score reached 67,88 and students who got the complete criteria of 19 students, in the cycle II reached an average score of 74,69 and students who received the complete criteria of 29 students, in the cycle III reached an average score of 82,69 and students who received the complete criteria of 34 students. From the results of the cycle that has been done the classroom action research activities using RBL learning model is said to work because the completeness of learning criteria reach 70 %. It is seen in the third cycle that reaches an average value of 82,69 and students who get the complete study criteria is 34 students means 85% of 40 students.